ANALISIS PERENCANAAN PARTISIPATIF PEMBANGUNAN TALUD PENAHAN LONGSOR (STUDI KASUS PERENCANAAN PEMBANGUNAN DI DESA LEREP KABUPATEN SEMARANG). - ANGGALIH, RATIH AYU TIRTA; ., Kushandajani (Journal of Politic and Government Studies, 2020)
In managing village development, each village government strives to improvedevelopment performance so that it can affect the welfare of the community. Therefore, insupporting development improvement performance needs to be supported by good development planning. Development planning is one of the strategies compiled by the village government in planning and managing village development, in which the government also engages the private sector and community groups in it, so that the implementation of regional development can be carried out properly and can realize the regionally planned vision and mission. This is supported by a high level of community participation with a percentage of attendance of up to 80% in musrenbang activities. The formulation of the problem in this research is how the participatory planning process of building a mudslide retaining slope in Lerep Village, Ungaran Barat Subdistrict, Semarang Regency and what are the inhibiting factors and factors that encourage community participation in the mudsliding retarding talud development project in Lerep Village, Semarang Regency.This research uses descriptive qualitative method with data collection techniquesthrough interviews and documentation. In this study, primary data obtained through directinterviews with informants determined from the linkage of the informants with researchproblems, and secondary data obtained from documentations of village community proposals,journals, articles, laws and regulations, news in print media , electronic or online media. While the data analysis in this study uses several considerations in partitionative planning, namely (1) Gathering information; (2) Channeling community aspirations; (3) Diversity of the decision making process.The results of this study indicate that overall community participation in infrastructuredevelopment planning can be said to be good. This is because the community and othercommunity members participate in every stage of development planning. In this study foundseveral supporting factors including: good coordination between residents and villageofficials, community activity, high levels of community awareness in mutual cooperation andthe existence of controls carried out by the community. While the inhibiting factors include: avery wide area coverage, busy people and the lack of adequate facilities.Lerep Village Government is expected to continue to increase openness in the form oftwo-way communication to the community, should make more efforts to stimulate and optimize community involvement and other community members.Keywords: Community participation, Development planning.